REPLACE OF INHARMONIC PERIODICAL SIGNALS WITH SERIES OF ROTATE PHASORS - MILLY, Miron (Trends in education, 2009)
In the paper is outing from inharmonic periodical function, developed to the complex form of Fourier series with exponential elements. The individual harmonic components of inharmonic periodical function are then under the rule of symbolicallycomplex method substitute with corresponding pertinent rotate phasors.
Keywords: inharmonic; periodical; function; phasor; Fourier series.